2022
DOI: 10.1186/s12912-022-01165-w
|View full text |Cite|
|
Sign up to set email alerts
|

Compliance with standard precautions and associated factors among undergraduate nursing students at governmental universities of Amhara region, Northwest Ethiopia

Abstract: Background Standard precautions are minimum infection control practices used to prevent the transmission of diseases and applied to all patient care. Nursing students are at high risk of exposure to occupational biologic hazards because they are obligated to provide care to patients admitted with unknown infection statuses. Compliance with standard precautions is an effective and efficient means of infection prevention. However, their compliance with standard precautions among nursing students … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…An optimal infection prevention climate is believed to drive workplace safety, representing the shared perception built by management to support safety regarding IPC in hospitals. 21 Workplace safety, influenced by the availability of zoning divisions, supply of quality personal protective equipment (PPE), and management of isolation for infectious patients, contributes to healthcare workers' adherence to standard precautions, thereby safeguarding patients from HAIs. 10,21 Thus, workplace safety is posited to be related to patient-centered care.…”
Section: Infection Prevention Climate Workplace Safety and Patient-ce...mentioning
confidence: 99%
See 2 more Smart Citations
“…An optimal infection prevention climate is believed to drive workplace safety, representing the shared perception built by management to support safety regarding IPC in hospitals. 21 Workplace safety, influenced by the availability of zoning divisions, supply of quality personal protective equipment (PPE), and management of isolation for infectious patients, contributes to healthcare workers' adherence to standard precautions, thereby safeguarding patients from HAIs. 10,21 Thus, workplace safety is posited to be related to patient-centered care.…”
Section: Infection Prevention Climate Workplace Safety and Patient-ce...mentioning
confidence: 99%
“…21 Workplace safety, influenced by the availability of zoning divisions, supply of quality personal protective equipment (PPE), and management of isolation for infectious patients, contributes to healthcare workers' adherence to standard precautions, thereby safeguarding patients from HAIs. 10,21 Thus, workplace safety is posited to be related to patient-centered care. Consequently, the following hypotheses are presented: H2: There is a relationship between infection prevention climate and workplace safety.…”
Section: Infection Prevention Climate Workplace Safety and Patient-ce...mentioning
confidence: 99%
See 1 more Smart Citation
“…However, one study has reported that, there is poor knowledge of students regarding infection control and prevention practices in undergraduate nursing programs [ 14 ]. Researcher reported that due to the nature of care, nursing students have more contact with patients than other students, according to these reports, more than half of nursing students had a history of needle sticks and more than a third of them had a history of contact with blood and secretions [ 15 ]. Another researcher stated that infection control programs should be added to the undergraduate curriculum [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Considering that the knowledge of nursing students about infection control is low [ 14 , 15 ] and since students have the responsibility of taking care of themselves, their families and patients, and on the other hand, nursing education teachers have the responsibility of revising the curriculum based on evidence, we decided to conduct a study with the aim of designing, implementing and evaluating the infection control program among undergraduate nursing students using a mixed study.…”
Section: Introductionmentioning
confidence: 99%